2017
DOI: 10.1038/s41598-017-06583-4
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry Imaging proves differential absorption profiles of well-characterised permeability markers along the crypt-villus axis

Abstract: Knowledge about the region-specific absorption profiles from the gastrointestinal tract of orally administered drugs is a critical factor guiding dosage form selection in drug development. We have used a novel approach to study three well-characterized permeability and absorption marker drugs in the intestine. Propranolol and metoprolol (highly permeable compounds) and atenolol (low-moderate permeability compound) were orally co-administered to rats. The site of drug absorption was revealed by high spatial res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 45 publications
(44 reference statements)
0
20
0
Order By: Relevance
“…The intestinal absorption behaviors of propranolol and metoprolol (high-permeability compounds) and atenolol (a lowpermeability compound) were evaluated by MALDI-MS imaging. (20) The results provided novel insight into site-specific absorption along the crypt-villus axis for each of the compounds, and confirmed a proximal-distal absorption gradient along the intestine. (20) In a tuberculosis research study, several anti-tuberculosis drugs including rifampicin, pyrazinamide, and moxifloxacin were administered to patients, and MALDI-MS imaging was used to visualize the distribution of these drugs in tuberculosis lesions.…”
Section: Maldi-ms Imaging As a Novel Methods For In Situ Visualizationmentioning
confidence: 59%
See 2 more Smart Citations
“…The intestinal absorption behaviors of propranolol and metoprolol (high-permeability compounds) and atenolol (a lowpermeability compound) were evaluated by MALDI-MS imaging. (20) The results provided novel insight into site-specific absorption along the crypt-villus axis for each of the compounds, and confirmed a proximal-distal absorption gradient along the intestine. (20) In a tuberculosis research study, several anti-tuberculosis drugs including rifampicin, pyrazinamide, and moxifloxacin were administered to patients, and MALDI-MS imaging was used to visualize the distribution of these drugs in tuberculosis lesions.…”
Section: Maldi-ms Imaging As a Novel Methods For In Situ Visualizationmentioning
confidence: 59%
“…(20) The results provided novel insight into site-specific absorption along the crypt-villus axis for each of the compounds, and confirmed a proximal-distal absorption gradient along the intestine. (20) In a tuberculosis research study, several anti-tuberculosis drugs including rifampicin, pyrazinamide, and moxifloxacin were administered to patients, and MALDI-MS imaging was used to visualize the distribution of these drugs in tuberculosis lesions. (27) The results revealed that rifampicin and pyrazinamide efficiently penetrated the tuberculosis infection sites in lung lesions but did not diffuse well in caseum.…”
Section: Maldi-ms Imaging As a Novel Methods For In Situ Visualizationmentioning
confidence: 59%
See 1 more Smart Citation
“…It provides insights into the biodistribution of compounds, while simultaneously generating data on pharmacodynamic biomarkers. Dr. Goodwin presented data from AZ that showed how the use of a range of multimodal imaging techniques improves understanding about compound efficacy, safety, and targeted drug delivery [ 32 , 33 ]. Investigating histopathological-targeted drug-induced toxicity is now readily achieved using high-spatial resolution and high-mass resolution IMS.…”
Section: Visualizing Drug Disposition In Tissuementioning
confidence: 99%
“…Absorption (F a ) is a combination of solubility and permeability and can be predicted with confidence in humans (Artursson and Karlsson, 1991;Fagerholm, 2007;Wei et al, 2009) and rats (Nilsson et al, 2017). In contrast, discrete measurement of F g , in vitro, has not been reported due to the lack of reliable assays derived from human intestinal sections.…”
Section: Introductionmentioning
confidence: 99%